2016
DOI: 10.1002/glia.23003
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes drive upregulation of the multidrug resistance transporter ABCB1 (P‐Glycoprotein) in endothelial cells of the blood–brain barrier in mutant superoxide dismutase 1‐linked amyotrophic lateral sclerosis

Abstract: The efficacy of drugs targeting the CNS is influenced by their limited brain access, which can lead to complete pharmacoresistance. We recently reported a tissue-specific and selective upregulation of the multidrug efflux transporter ABCB1 or P-glycoprotein (P-gp) in the spinal cord of both patients and the mutant SOD1-G93A mouse model of amyotrophic lateral sclerosis (ALS), a fatal neurodegenerative disease that prevalently kills motor neurons. Here, we have extended the analysis of P-gp expression in the SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 63 publications
4
75
0
Order By: Relevance
“…Although the underlying connection between different genetic forms of ALS is complex and at this time unclear, this work indicates that strategies targeting astrocyte contributions to disease may be useful for a variety of ALS cases. Although future work must be done to confirm these findings in vivo and, eventually in patients, we recently confirmed the clinical relevance of our findings showing that in a patient‐derived in vitro model of the blood–brain‐barrier, iPSC‐derived astrocytes from a mutFUS patient, drive drug‐efflux transporter mediated pharmacoresistance through TNFα (Qosa et al, 2016). Thus, underscoring the role of TNFα in driving mutFUS‐ALS through astrocytes and identifying TNFα as an important therapeutic target in this form of the disease.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although the underlying connection between different genetic forms of ALS is complex and at this time unclear, this work indicates that strategies targeting astrocyte contributions to disease may be useful for a variety of ALS cases. Although future work must be done to confirm these findings in vivo and, eventually in patients, we recently confirmed the clinical relevance of our findings showing that in a patient‐derived in vitro model of the blood–brain‐barrier, iPSC‐derived astrocytes from a mutFUS patient, drive drug‐efflux transporter mediated pharmacoresistance through TNFα (Qosa et al, 2016). Thus, underscoring the role of TNFα in driving mutFUS‐ALS through astrocytes and identifying TNFα as an important therapeutic target in this form of the disease.…”
Section: Discussionsupporting
confidence: 74%
“…Chimeric mice in which mutant SOD1 was selectively deleted in astrocytes showed substantially slowed disease progression (Yamanaka et al, 2008) while both rodent and human patient‐derived astrocytes have been shown to play a toxic role through the release of, yet identified, soluble factors [reviewed (Haidet‐Phillips et al, 2011; Lasiene and Yamanaka, 2011). Furthermore, we recently showed that ALS astrocytes, including mutFUS expressing patient astrocytes, drive up‐regulation of the multidrug resistance transporter P‐Glycoprotein (P‐gp) in endothelial cells of the blood‐brain barrier (Qosa et al, 2016). Astrocytes participate in disease also through a “loss of function” [reviewed (Maragakis and Rothstein, 2006)] as demonstrated by several human and rodent studies that have observed defects and/or loss of astrocytic glutamate transporter EAAT2/GLT1 for several ALS subtypes including SOD1‐ALS (Benkler, Ben‐Zur, Barhum, & Offen, 2013; Howland et al, 2002) sALS (Lin et al, 1998), and C9orf72‐ALS (Kwon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in mixed neuron/astrocyte cultures subjected to oxygen-glucose deprivation, astrocytes are the sole locus for Nrf2 activation in response to oxidative stress [42, 43]. Interestingly, a new study has shown that astrocytes with mutant SOD1 increase P-glycoprotein in endothelial cells in vitro [44]. Moreover, astrocytic Nrf2 activation helps to prevent oligodendrocyte loss and demyelination in an animal model of multiple sclerosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…ABCB1, one of the members of the ABC transporter family involved in multidrug resistance, is upregulated in endothelial cells of the brain capillaries in ALS. In blood-brain barrier models, the expression of mutant hSOD1 and mutant FUS in astrocytes drives ABCB1 upregulation in endothelial cells [201]. Thus, the potential role of astrocytes affecting drug bioavailability may need to be addressed in order to implement effective drug therapies in ALS.…”
Section: Therapeutic Potential Of Astrocytesmentioning
confidence: 99%